Cytokine and antibody production during murine leptospirosis - Marinho,M. (2006)
The aim of the present study was to investigate the kinetics of humoral and cellular responses during leptospirosis. We observed that the presence of tumor necrosis factor-alpha (TNF-alpha) and interleukin-6 (IL-6) was associated with antibody production and bacterial recovery, and the compromising of both TNF-alpha and IL-6 in the immunopathogenesis of leptospirosis during an experimental infection of BALB/c mice inoculated with Leptospira interrogans serovar Canicola was verified. Results showed higher levels of TNF-alpha and IL-6 in the initial phase of infection, in which the greatest bacterial clearance was observed. However, when the bacterial recovery was compared with the kinetics of the production of antibodies, the results revealed a kinetics proportionally inverted to antibody production. This fact may be related to some inhibitory factor which could be responsible for the selective suppression of the cellular immune response. We concluded that during leptospirosis there was a greater mobilization of the cellular immune response activity, mainly in the initial phase of the infectious process, for posterior involvement of the humoral response, and that both TNF-alpha and IL-6 could be associated with the immunopathogenesis of the disease.